Mapping the Network of Social Cognition Domains in Children With Autism Spectrum Disorder Through Graph Analysis - Pino, Maria Chiara; Vagnetti, Roberto; Masedu, Francesco; Attanasio, Margherita; Tiberti, Sergio; Valenti, Marco; Mazza, Monica (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) children are characterised by difficulties in social cognition (SC) domains. The aim of this study is to build a SC network to explore associations among interacting elements within this cognitive construct. We used a graph analysis to explain how individual SC domains relate to each other and how these relations may differ between ASD and typically developing (TD) groups. Seventy-six ASD and 81 TD children, matched for verbal mental age, were subjected to three SC measures. Our results showed that TD children exhibited a SC network characterised by a single domain (i.e. Social Cognition); while children with ASD demonstrated communicating node communities where Social Information Processing measured by SIPI represents a key point in understanding network differences between groups.